Occupational exposure to blood and body fluids and use of human immunodeficiency virus post-exposure prophylaxis amongst nurses in a Gauteng province hospital - Melitah M. Rasweswe; Mmapheko D. Peu (AOSIS, 2020)
Background: Healthcare facilities in South Africa are confronted by several challenges arising from Human immunodeficiency virus (HIV) and acquired immune diseases syndrome infection pandemic. All categories of nurses continue to experience accidental occupational exposure to blood and body fluids (BBFs) of patients who are HIV-positive. Studies conducted revealed that nurses fail to report the occurrence of the exposures. This represents a serious challenge because they contract HIV infections whilst in the process of helping others. Objectives: The purpose of this study was to determine the occupational exposures and use of HIV post-exposure prophylaxis (PEP) amongst nurses at the selected tertiary academic hospital, Tshwane district, Gauteng province, South Africa. Methods: A quantitative descriptive study was conducted with 94 male and female clinical nurses, using a self-administered questionnaire that facilitated collection of biographical data, occupational exposures to BBFs and use of HIV PEP. The data analysis included univariate and bivariate descriptive analyses. Results: Of the 94 nurses, n = 40 (43%) had been exposed to BBFs, either through sharp or needle prick injuries or splashes but only 16 (46%) of them reported the incident. Nurses were not keen to report accidental occupational exposures to BBFs in their own facility and rather sought HIV PEP outside their workplace. They gave different reasons for their behaviour. For example, 'I did not know where to report'. Conclusion: Our study highlights the gaps that exist in reporting occupational exposure to BBFs and obtaining HIV PEP. Therefore, we recommend evaluation of these occupational exposures to BBFs and the management thereof, as well as to address the identified problems.